Age-associated changes in the mechanical properties of human cadaveric pelvic floor muscles. (2nd January 2020) - Burnett, Lindsey A.; Cook, Mark; Shah, Sameer; Michelle Wong, Ms.; Kado, Deborah M.; Alperin, Marianna
Abstract: Proper function of the female pelvic floor requires intact pelvic floor muscles (PFMs). The prevalence of pelvic floor disorders (PFDs) increases substantially with age, in part due to clinically identified deterioration of PFM function with age. However, the etiology of this decline remains largely unknown. We previously demonstrated that PFMs undergo age-related fibrotic changes. This study sought to determine whether aging also impacts PFMs' passive mechanical properties that are largely determined by the intramuscular extracellular matrix. Biopsies from younger (≤52y) and older (>52y) female cadaveric donors were procured from PFMs, specifically coccygeus (C) and two portions of the levator ani - iliococcygeus (IC) and pubovisceralis (PV), and the appendicular muscles - obturator internus (OI) and vastus lateralis (VL). Muscle bundles were subjected to a passive loading protocol, and stress-sarcomere length (Ls ) relationships calculated. Muscle stiffness was compared between groups using 2-way ANOVA and Sidak pairwise comparisons, α < 0.05. The mean age was 43.4 ± 11.6y and 74.9 ± 11.9y in younger (N = 5) and older (N = 10) donors, respectively. In all PFMs, the quadratic coefficient of parabolic regression of the stress-Ls curve, a measure of stiffness, was lower in the younger versus older group: C: 33.7 ± 13.9 vs 87.2 ± 10.7, P  = 0.02; IC: 38.3 ± 12.7 vs 84.5 ± 13.9, P  = 0.04; PV: 24.7 ± 8.8 vs 74.6 ± 9.6, P  = 0.04. In contrast, non-PFM stiffness was not affected by aging: OI: 14.5 ± 4.7 vs 32.9 ± 6.2, P  = 0.8 and VL: 13.6 ± 5.7 vs 30.1 ± 5.3, P  = 0.9. Age-associated increase in PFM stiffness is predicted to negatively impact PFM function by diminishing muscle load-bearing, excursional, contractile, and regenerative capacity, thus predisposing older women to PFDs.